(3GdhSGFd Edi eYQaI GdeSGFds - (3EOQjS Hf Ydj Gdchajs
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb GdNdb ef ZjQ MGLI (B... (3CeG HYO aEfj JUaMJ HYV cJH GdYdeGA (B... (3aCMHHJ Cf GVY dPdc OaJQG jcTa Yf Jdc GdOQ GdfajS (B...s
(3BNQgG (B:s
(3aj Ydej HYjfg hjhVMg Cfg(B... (3hjSJhaj GdebOQ aj hbJ hGMO hbO jSJhaj GdebOQ hde jOd (B...(3aGLJeGY GdSjO gh CHYO GdCLdjf(B...(3bGd GdaGVd GdTGQM(B: (3GdMSfGJ geG GdSeY hGdHUQ(B...s
(3JHUQI GdYfhGf (B:s
(3GdQSGFd Edi Yde Jdc GdeSGFds
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis